Asthma awareness among primary school teachers in Zanjan in 2014 - Iraj Mohammadzadeh (Caspian Journal of Pediatrics, 2017)
Background: Asthma is the most common chronic respiratory disease and a leading cause of school absenteeism. Awareness, attitude, and knowledge of asthma can play an effective role in controlling this disease and its consequences. Accordingly, this study aimed to determine the level of asthma awareness among primary school teachers in Zanjan. Methods: This descriptive cross-sectional study was conducted on 403 teachers of boys- and girls-only primary schools, who were selected using single-stage cluster sampling. Data were collected using a researcher-made questionnaire, in which higher scores indicated higher level of asthma awareness. Findings were analyzed using descriptive and analytical statistics in SPSS. Results: Data analysis showed that 58 (14.4%) and 345 (85.6%) out of 403 participants were male and female, respectively. The means of age and work experience of the participants were 45±5.53 and 22±5.92 years old, respectively. In addition, teachers’ mean score for asthma awareness was at a good level (12±2.2). Teachers’ mean level of asthma awareness had a significant relationship with gender and history of dealing with asthmatic children (p = 0.03, p = 0.04), while it had no significant relationship with age, work experience, and education level. Conclusion: In this study, the mean level of asthma awareness among the primary school teachers was good. Due to the importance of the disease in children and effective role of teachers in helping them, effective measures must be taken to increase teachers’ awareness.